ChemInform Abstract: KOtBu‐Mediated Aerobic Transition‐Metal‐Free Regioselective β‐Arylation of Indoles: Synthesis of β‐(2‐/4‐Nitroaryl)‐indoles. Issue 22 (15th May 2015) - Kumar, Shailesh; Rathore, Vandana; Verma, Ajay; Prasad, Ch. Durga; Kumar, Amit; Yadav, Abhimanyu; Jana, Sadhan; Sattar, Moh.; Meenakshi, Meenakshi; Kumar, Sangit
Abstract: β‐Arylation in unprotected indoles can be achieved chemo‐ and regioselectively by employing KO t Bu at room temperature in air without using a transition metal catalyst and aryl halide coupling partner.